2013
DOI: 10.1093/jac/dkt224
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of compensatory evolution in strains carrying rpoB Ser531Leu, the rifampicin resistance mutation most frequently found in clinical isolates

Abstract: The compensatory mutations identified in Salmonella cluster in similar locations to the additional mutations found in M. tuberculosis isolates. These new data strongly support the idea that many of the previously identified rpoA, rpoB and rpoC mutations in rifampicin-resistant M. tuberculosis (rpoB S531L) are indeed fitness-compensatory mutations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
78
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(84 citation statements)
references
References 19 publications
5
78
0
1
Order By: Relevance
“…Indeed, it was reported that part of rifampicin‐resistant isolates with a rpo B mutation also carry a nonsynonymous mutation in the rpo A or rpo C gene in South Africa (27.1%, 89/329), China (27.8%, 89/320) and Korea (39.4%, 67/170) (Comas et al., 2012; Li et al., 2016; Song et al., 2014). In addition, clinical isolates that carry mutations in the RRDR of rpo B and also in rpo A/ rpo C display higher competitive fitness in vitro and in vivo compared with laboratory‐generated rifampicin‐resistant mutants that carry only the same rpo B RRDR mutation and that belong to the same phylogenetic lineage (Brandis & Hughes, 2013; Comas et al., 2012; Song et al., 2014). These data suggest that mutations in the rpo A/ rpo C genes are fitness‐compensatory mutations that alleviate the costs of rpo B mutations.…”
Section: Compensatory Mutationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Indeed, it was reported that part of rifampicin‐resistant isolates with a rpo B mutation also carry a nonsynonymous mutation in the rpo A or rpo C gene in South Africa (27.1%, 89/329), China (27.8%, 89/320) and Korea (39.4%, 67/170) (Comas et al., 2012; Li et al., 2016; Song et al., 2014). In addition, clinical isolates that carry mutations in the RRDR of rpo B and also in rpo A/ rpo C display higher competitive fitness in vitro and in vivo compared with laboratory‐generated rifampicin‐resistant mutants that carry only the same rpo B RRDR mutation and that belong to the same phylogenetic lineage (Brandis & Hughes, 2013; Comas et al., 2012; Song et al., 2014). These data suggest that mutations in the rpo A/ rpo C genes are fitness‐compensatory mutations that alleviate the costs of rpo B mutations.…”
Section: Compensatory Mutationsmentioning
confidence: 99%
“…These data suggest that mutations in the rpo A/ rpo C genes are fitness‐compensatory mutations that alleviate the costs of rpo B mutations. Furthermore, genetic reconstructions in a Salmonella model demonstrated that mutations not only in rpo A and rpo C, but also in rpo B are associated with higher growth rate (Brandis & Hughes, 2013; Brandis et al., 2012). In fact, many previous studies showed that rifampicin‐resistant M. tuberculosis clinical isolates carry multiple (double, triple and quadruple) mutations in the rpo B gene (Bahrmand, Titov, Tasbiti, Yari, & Graviss, 2009; Casali et al., 2014; Nguyen, Nguyen, et al., 2017; Song et al., 2014).…”
Section: Compensatory Mutationsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, another study reported that phenotypic testing indicated isoniazid resistance, but WGS failed to identify the mutation responsible (45). Mutations conferring drug resistance are known to come at the cost of a loss in an organism's fitness; however, recent genomic studies revealed that compensatory mutations can occur which overcome the loss of fitness and create a "perfect storm" of resistant isolates without reduced fitness (42,(46)(47)(48). Furthermore, it has been shown that M. tuberculosis strains of different lineages can differ in their virulence, acquiring mutations conferring antibiotic resistance, a delayed host immune response, enhanced transmissibility, and more severe disease at different rates (49)(50)(51).…”
Section: Genomics For Predicting Antibiotic Susceptibility Of M Tubementioning
confidence: 99%